2021
DOI: 10.21831/jpipfip.v14i2.41450
|View full text |Cite
|
Sign up to set email alerts
|

Google Classroom: The Web-Based Media for Teaching English

Abstract: This study investigates whether: 1) Google Classroom is more effective than the conventional method for teaching writing; 2) The high creativity students have better writing skills than those who have low creativity, and; 3) Interaction between teaching method and students’ creativity in teaching writing occurs. This quasi-experimental study was conducted at STMIK Pringsewu in the academic year of 2020/2021.  The sample of this research was two classes, the namely experimental class taught using Google Classro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…It can be concluded that the use of google classroom is effective in learning to write recount texts for class X students of SMK Batik Perbaik for the academic year of 2021/2022. The result are in line with (Andewi & Pujiastuti, 2021), (Laili & Muflihah, 2020), (Yunus & Syafi'i, 2020), and (Daulay et al, 2021). The result of those four articles showed that the use of Google Classroom t in teaching writing can improve students'writing skill.…”
Section: C) Test Of Experimental Significancesupporting
confidence: 60%
“…It can be concluded that the use of google classroom is effective in learning to write recount texts for class X students of SMK Batik Perbaik for the academic year of 2021/2022. The result are in line with (Andewi & Pujiastuti, 2021), (Laili & Muflihah, 2020), (Yunus & Syafi'i, 2020), and (Daulay et al, 2021). The result of those four articles showed that the use of Google Classroom t in teaching writing can improve students'writing skill.…”
Section: C) Test Of Experimental Significancesupporting
confidence: 60%
“…Whereas Google Classroom has many interesting features, one of which is the easy task collection feature (Andewi & Pujiastuti, 2021). Besides that, Google Classroom integrated with other product applications from Google which can support the use of this application.…”
Section: Discussionmentioning
confidence: 99%
“…This medium is evolving as a positive example of technology because it provides a flexible and individualized learning environment that makes use of learning outside the classroom. Google Classroom provides a number of features that can assist in simplifying the assessment procedures of assignments and exams without the use of paper, which is an advantage of online learning (Andewi & Dwi, 2021). This is a new challenge in delivering education in a variety of ways, such as the convenience provided by Google Classroom to students and teachers (Northey, Bucic, Chylinski, & Govind, 2015).…”
Section: International Journal Of Social Science Research and Reviewmentioning
confidence: 99%